2022
DOI: 10.3390/agronomy12123216
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Non-Photochemical Quenching Traits in Oryza sativa L.

Abstract: Manipulating the photoprotective mechanism has been demonstrated to be an effective way to enhance the photosynthetic productivity of crop plants. NPQ(T) is a chlorophyll fluorescence parameter for rapid estimation and imaging of non-photochemical quenching (NPQ) of excitons in the photoprotective mechanism. However, the variation and genetic basis of NPQ(T) are rarely reported in the Oryza sativa L. In this study, we collected 173 rice cultivars and investigated the NPQ(T) value. We found that the NPQ(T) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Despite the challenges associated with GBS, it is still a cost-effective, high-throughput, and minimally invasive method, making it suitable for large-scale studies of diverse crop populations. GBS can capture rare and low-frequency genetic variants that may not be detected by other genotyping methods, providing a more comprehensive view of the genetic architecture underlying BLB resistance [29,60,97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges associated with GBS, it is still a cost-effective, high-throughput, and minimally invasive method, making it suitable for large-scale studies of diverse crop populations. GBS can capture rare and low-frequency genetic variants that may not be detected by other genotyping methods, providing a more comprehensive view of the genetic architecture underlying BLB resistance [29,60,97].…”
Section: Discussionmentioning
confidence: 99%
“…Variant were called using the Genome Analysis Toolkit (GATK) software v 4.2.3.0 [42,58] where SNPs and insertions-deletions (indels) were named using the GVCF analysis, and variants were grouped using GATK's CombineGVCFs function [59]. The joint call step was then performed using genotypeGVCFs of the GATK software [60], followed by SNP extraction using SelectVariantsGATK based on the reference genome.…”
Section: Genotyping Preparationmentioning
confidence: 99%
“…Both crops and wild species exhibit substantial natural variation in NPQ (Jung and Niyogi 2009;Rungrat et al 2019;Gamba et al 2022;Wei et al 2022). A study of the maximum NPQ induction in rice (Oryza sativa) identified 33 loci, including the rice ortholog of PSBS (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%